Potential of 'stacking' early childhood interventions to reduce inequities in learning outcomes - Molloy, Carly; O'Connor, Meredith; Guo, Shuaijun; Lin, Colleen; Harrop, Christopher; Perini, Nicholas; Goldfeld, Sharon (My University, 2019)
Early childhood interventions are critical for reducing child health and development inequities. While most research focuses on the efficacy of single interventions, combining multiple evidence-based strategies over the early years of a child's life may yield greater impact. This study examined the association between exposure to a combination of five evidence-based services from 0 to 5 years on children's reading at 8-9 years. Data from the nationally representative birth cohort (n=5107) of the Longitudinal Study of Australian Children were utilised. Risk and exposure measures across five services from 0 to 5 years were assessed: antenatal care, nurse home-visiting, early childhood education and care, parenting programme and the early years of school. Children's reading at 8-9 years was measured using a standardised direct assessment. Linear regression analyses examined the cumulative effect of five services on reading. Interaction terms were examined to determine if the relationship differed as a function of level of disadvantage. A cumulative benefit effect of participation in more services and a cumulative risk effect when exposed to more risks was found. Each additional service that the child attended was associated with an increase in reading scores (b=9.16, 95% CI=5.58 to 12.75). Conversely, each additional risk that the child was exposed to was associated with a decrease in reading skills (b=-14.03, 95% CI=-16.61 to -11.44). Effects were similar for disadvantaged and non-disadvantaged children. This study supports the potential value of 'stacking' early interventions across the early years of a child's life to maximise impacts on child outcomes.
Keywords: child development; child inequities; cumulative benefit; cumulative risk; early childhood interventions; socioeconomic disadvantage; Disadvantage, adversity and resilience; Childhood and child development; Health and wellbeing